The Authenticity of Micro-influencers Producing Paid Content for Social Media in Viet Nam - Pham, Phuong Anh (2023)
Recently, influencer marketing is not only welcomed by brands, but the topic also attracts scholars’ attention. With the rise of e-commerce, social media and influencer marketing in Viet Nam, many brands can easily reach out to micro-influencer for collaborations to promote products and drive sales on e-commerce and social media platforms. Therefore, the micro-influencers’ authenticity management should be deepened to help both micro-influencers and brands decide suitable strategies in their partnerships. This study aims to understand the authenticity of micro-influencers producing paid content for social media in Viet Nam. The focus is on three views: 1) Understanding key features of content marketing in Viet Nam and how they have supported and propelled the development of micro-influencer in Viet Nam; 2) Expanding the current definitions and knowledge of micro-influencers and investigating the authenticity of Vietnamese micro-influencers and its beneficial effects; 3) The management of collaborations with micro-influencers in Viet Nam to increase authenticity. The study used qualitative research and abductive reasoning to collect data. By using purposive sampling, 12 semi-structured interviews were conducted. The research employed thematic analysis to analyze the gathered data. The findings of this study showed that changes in content marketing and social media enable changes in micro-influencer marketing. The study results indicated that authenticity is a complex concept with various elements and as micro-influencers’ authenticity have various benefits, to increase their authenticity, micro-influencers should 1) Be true and consistent; 2) Ensure a good brand fit; 3) Be transparent about the collaborations. Moreover, the results implied that brands should carefully check the brand fit to select micro-influencers, give them the creative freedom, transparently disclose the partnerships, and build long-term partnerships instead of on-off ones to make the collaborations more authentic. The findings also suggested possible trends in micro-influencer marketing in Viet Nam. Overall, this study has broadened the current understanding of the subject and offered various managerial implications and directions for further research.